THE RELATION OF MENARCHE AND OBESITY WITH THE INCIDENCE OF BREASTCANCER IN WOMEN OF CHILDBEARING AGE AT RSPAL DR. RAMELAN SURABAYA - Rahmadhani, Herin Setyaning; F., Euvanggelia Dwilda; Djuari, Lilik (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2024)
Breastcancer is an evil for women in the world. The incidence of breastcancer in women of childbearing age (WUS) increases every year including at RSPAL dr. Ramelan Surabaya, from 389 to 457 cases (14.87%) during 2022. This research was conducted at Surgical Oncology Polyclinic RSPAL dr. Ramelan Surabaya toward WUS. This study was an analytical observational study with a case control design, breast cancer in WUS as the case group and no breast cancer in WUS as the control group. The dependent variable is breast cancer on WUS, while the independent variables are menarche and obesity. The sample size was 160 respondents, consisting of 80 case groups and 80 control groups. The sampling method uses simple random sampling. To determine the relationship between variables, the data collected was tested using the chi-square test with a significance level of α=0.05. The results showed that most of the obese (75%) were included in the case group. The results of the Chi-square analysis of breast cancer in WUS with menarche showed p value=0.421 (p>0.05), For breastcancer in WUS with obesity, the chi-square analysis showed p value=0.001 (p<0.05), meaning that there is a relationship between obesity and the incidence of breast cancer in WUS.